Plant culture construction and plant diversity protection and management in the China national botanical garden - Feifei LI; Binsheng LUO; Xia CUI; Chunlin LONG (Guangxi Zhiwu, 2023)
Biological culture is of great significance to the conservation of biodiversity. The formation and development of botanical gardens have reflected the plant culture which formed by human beings due to material and spiritual needs in history. Modern botanical gardens have made outstanding achievements in plant ex-situ protection, while the plant culture construction is still a little insufficient. In the process of global biodiversity conservation, the important roles of traditional culture in biodiversity conservation and sustainable use of biological resources have been increasingly valued. At this background, this study emphasized the close connection and co-evolution relationship between biocultural diversity and biodiversity, and reviewed the implication of plant culture in early botanical gardens and Chinese classical gardens. And through the analysis of the main functions of 3 085 modern botanical gardens around the world, we found that only 7.36% of botanical gardens carried out ethnobotanical research, while 11.18% carried out conservation biology research, and 17.18% worked out a plant conservation programme, which revealed the improvement of the protection function and the weakening of the cultural function of modern botanical gardens. Based on the demand for the construction of plant culture in the effective protection of plant diversity in the current botanical garden, this study further analyzed the deficiencies of plant culture construction in botanical gardens in China, including: (1) insufficient plant culture information data in plant species diversity information; (2) lack of consideration of benefit-sharing of traditional knowledge in biodiversity conservation; (3) lack of theme parks that display plant diversity with culture. Focused on the goal of plant diversity conservation and management in the China national botanical garden, we put forward the following suggestions on plant culture construction in the China national botanical garden system from three aspects, in order to provide a reference for the construction of a national botanical garden system with the characteristics of Chinese ecological civilization. Plant diversity protection and utilization: to strengthen the consideration of plant culture in the construction of plant diversity information and germplasm resource bank, encourage ethnobotanical research. Benefit-sharing: to establish access and benefit-sharing (ABS) standard procedures covering traditional knowledge to ensure fair and equitable benefit-sharing. Public participation: to consider display the regionality and uniqueness in China national botanical garden, and add ethnic plant culture theme parks or exhibition halls.